Accounting Information System in the Digital Economy in Vietnam - Duong Thi Quynh Lien (Journal La Bisecoman, 2021)
The industrial revolution 4.0 in general and the trend of the digital economy in particular have affected all aspects of the economy. The requirements of finance and digital accounting, as well as the requirements of regional and international financial and accounting integration, require proactive preparation, taking full advantage of the advantages as well as limiting the impacts. disadvantage. That context is posing a requirement to innovate the accounting information system in the digital technology era. Therefore, learning about the impact of the digital economy on the accounting information system: accounting process, accounting human resources, and state management of accounting is essential to ensure the system effective accounting system, helping businesses seize opportunities and overcome challenges.